Electrospinning collagen complex, preparation method and application

Through the preparation method of electrospun collagen complex, electrospun I-type collagen matrix and complex MQA are combined to form electrospun collagen complex MQA, which solves the difficulty of the existing technology to achieve multi-layer hard tissue in caries at the same time. The repair problem has achieved the repair effect of enamel, dentin bionic mineralization and dental pulp cell differentiation.

CN119424391AActive Publication Date: 2025-02-14SICHUAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510038332.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-02-14
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The prior art is difficult to achieve the repair effect of enamel, dentin bionic mineralization and dentin differentiation in caries, especially in cases of severe dentin damage.

Method used

The electrospun collagen complex is prepared by electrospun type I collagen matrix and the complex MQA (composed of polypeptide QP5, amorphous calcium phosphate ACP and mesoporous silica MSN) to form an electrospun collagen complex. MQA-Col, realizes the repair of enamel, dentin bionic mineralization and dental pulp cell differentiation.

Benefits of technology

The bionic repair effect of caries lesions integrating enamel bionic mineralization, dentin bionic mineralization and promoting pulp cell formation to dentin differentiation is achieved, and the repair efficiency and effect of dental tissue is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424391A_ABST
    Figure CN119424391A_ABST
Patent Text Reader

Abstract

The invention discloses an electrospun collagen complex as well as a preparation method and application thereof, and belongs to the technical field of biological materials. The preparation method disclosed by the invention comprises the following steps: S1, preparing a complex MQA; s2, preparing an electrostatic spinning type I collagen matrix Col; and S3, preparing a suspension from the complex MQA by using a chitosan-acetic acid solution, dipping an electrostatic spinning type I collagen matrix Col in the suspension, carrying out ultrasonic treatment, taking out the electrostatic spinning type I collagen matrix Col, cleaning, and drying to obtain the electrospun collagen complex. The invention also discloses the electrospun collagen complex prepared by the method, and application of the electrospun collagen complex in preparation of medicines for preventing or / and treating decayed teeth. The electrospun collagen complex provided by the invention can realize a caries bionic repair effect integrating enamel biomimetic mineralization, dentin biomimetic mineralization and promotion of dental pulp cells to dentin differentiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomaterials, and specifically relates to an electrospun collagen complex, a preparation method and an application thereof. Background Art

[0002] Caries is one of the most common chronic diseases worldwide, affecting 60% to 90% of children and the vast majority of adults. It has a significant impact on the economic status and quality of life of patients and imposes a heavy burden on the public health system. Typical caries lesions begin with demineralization under the surface of the enamel, then gradually develop into the deeper layers, invading the dentin, causing the loss of minerals inside and outside the type I collagen in the dentin layer and structural damage, and eventually progressing to the destruction of the pulp-dentin complex, causing pulp infection. According to the International Caries Classification and Management System, caries can be divided into early caries (limited to the enamel layer), moderate caries (involving dentin) and deep caries (extensive destruction of dentin and even involving the pulp cavity) according to their degree of progression. The degree of progression, affected areas and pulp status of different types of caries are different, which directly affects the effect of clinical tooth restoration treatment.

[0003] At present, clinical treatments for different types of caries mostly rely on simple surface mineralization and mechanical filling based on resin-based materials. However, in cases where dentin damage is more severe, bacteria and other stimuli can further infect the pulp tissue through the dentinal tubules, leading to irreversible pulp damage. How to more effectively repair these damaged tooth tissues has become a major challenge in the treatment of caries.

[0004] In recent years, guided by the concept of bionics, the bionic restoration theory that uses effector molecules of biomimetic natural tooth development regulatory factors and aims to imitate the microstructure of the tooth has gradually become a new direction in the research of caries prevention and treatment. This bionic restoration method is mainly divided into two directions: enamel bionic restoration and dentin bionic restoration. Enamel bionic restoration focuses on using nucleation templates to guide calcium-phosphorus deposition and nucleation growth to form orderly arranged nanorod-shaped new hydroxyapatite (HAP), thereby reversing the demineralization under the enamel surface and replenishing the HAP crystals lost in the demineralized area. The bionic mineralization of dentin requires that the demineralized dentin collagen fibers re-mineralize in an orderly manner within and between fibers, so that the HAP nucleation precursors, mainly in the form of amorphous calcium phosphate (ACP), are backfilled into the demineralized fibers, and finally a dentin bionic mineralization layer with mechanical strength is formed. Although existing biomimetic mineralization research has made some progress in mineralization effects, most studies are still limited to a single stage of caries development and a single subject, ignoring the fact that caries lesions often involve multiple layers of tooth hard tissue at the same time in clinical practice, and are often accompanied by damage to the pulp-dentin complex. At present, the research on enamel biomimetic mineralization, dentin biomimetic mineralization and activation of pulp cell reparative response each involves different mechanisms and targets. There is no single effector that can achieve these three effects at the same time, and various known active ingredients also lack organic integration guided by multi-dimensional effects.

[0005] Amelogenin is a non-glycosylated protein secreted by ameloblasts and is the main component of enamel matrix proteins. During the mineralization and maturation of enamel, amelogenin participates in the initiation of mineralization, stabilizes ACP, regulates the growth of HAP and guides its arrangement, thus playing an important role in enamel development.

[0006] ACP is an important biomimetic precursor that has been widely studied in the field of mineralization. As an amorphous calcium phosphate substance, ACP has the ability to crystallize in an orderly manner and form a specific crystal structure HAP. Based on the non-classical crystallization theory and the polymer-induced liquid precursor theory, under the action of polymer stabilizers such as polyacrylic acid, ACP can be maintained in a liquid mineral precursor state, and then infiltrate demineralized enamel or collagen fibers to form enamel crystals and crystals within dentin fibers, thereby providing continuous and controlled biomimetic mineralization raw materials. However, the disadvantage of difficult enrichment of liquid phase ACP limits its application in the field of biomineralization. Early studies often prepared ACP in the form of anhydrous particles and added it to dental filling materials such as resins and glass ionomers, but the uncontrollable agglomeration of ACP directly affected the mechanical properties of the filling materials.

[0007] Therefore, providing a substance that can simultaneously achieve the three-way repair effects of enamel and dentin bionic mineralization and odontoblast differentiation of dental pulp cells in caries has become an urgent problem to be solved by those skilled in the art. Summary of the invention

[0008] One of the purposes of the present invention is to provide a method for preparing an electrospun collagen complex, which has a simple process and is easy to operate. The electrospun collagen complex prepared by this method can achieve a bionic repair effect of caries lesions that integrates enamel bionic mineralization, dentin bionic mineralization and promotion of dentinogenesis into dental pulp cells.

[0009] The second object of the present invention is to provide an electrospun collagen complex prepared by the method.

[0010] The third object of the present invention is to provide applications of the electrospun collagen complex.

[0011] To achieve the above purpose, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention discloses a method for preparing an electrospun collagen complex, the method comprising the following steps: S1. Preparation of complex MQA: S11. Preparation of PAH-Ca solution: 2+ The buffer solution is mixed with polyacrylamide hydrochloride to obtain a PAH-Ca solution; S12. Preparing a PAH-ACP solution: adding an aqueous phosphate solution to the PAH-Ca solution and mixing well to obtain a PAH-ACP solution; S13. The polypeptide QP5 and the porous carrier are added to the PAH-ACP solution, stirred, centrifuged, and the precipitate is washed and dried to obtain the complex MQA; S2. Preparing electrospun type I collagen matrix Col: dissolving freeze-dried type I collagen sponge in an organic solvent to prepare a freeze-dried type I collagen sponge solution; converting the solution to prepare electrospun collagen by electrospinning; and then cross-linking the electrospun collagen, washing, and drying to obtain an electrospun type I collagen matrix Col; S3. The complex MQA is prepared into a suspension with chitosan-acetic acid solution, and the electrospun type I collagen matrix Col is immersed in the suspension, subjected to ultrasonic treatment, and the electrospun type I collagen matrix Col is taken out, washed, and dried to obtain the electrospun collagen complex.

[0012] In some embodiments of the present invention, the Ca-containing 2+ The buffer is a buffer containing CaCl2, and its pH value is 6.8 to 7.2, such as; in some embodiments of the present invention, Ca 2+ The pH value of the buffer is 6.8, 6.9, 7.0, 7.1 or 7.2, preferably 7.0; The phosphate aqueous solution includes a K2HPO4 buffer or a Na2HPO4 buffer, and its pH value is 5.0 to 6.0; in some embodiments of the present invention, the pH value of the phosphate aqueous solution is 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9 or 6.0, preferably 5.5; The porous support includes mesoporous silica.

[0013] In some embodiments of the present invention, the Ca in the PAH-Ca solution is 2+ The concentration was 16-20 mM, and the concentration of polyacrylamide hydrochloride was 580-620 μg / mL; The concentration of phosphate in phosphate aqueous solution is 8~9 mM. The volume ratio of PAH-Ca solution to phosphate aqueous solution is 0.8-1.2: 1. In step S13, the mass ratio of polypeptide QP5 to porous carrier is 1: 2-3; the mass volume ratio of porous carrier to PAH-ACP solution is 3-4: 1, wherein when the mass unit of porous carrier is mg, the volume unit of PAH-ACP solution is ml.

[0014] In some embodiments of the present invention, the organic solvent in step S2 includes a mixed solution of hexafluoroisopropanol and acetic acid, and the volume ratio of hexafluoroisopropanol to acetic acid is 0.5-2:1; The concentration of freeze-dried type I collagen in the freeze-dried type I collagen sponge solution is 80-100 mg / mL; In step S2, glutaraldehyde vapor volatilization crosslinking or EDC / NHS solution crosslinking is used; preferably glutaraldehyde vapor volatilization crosslinking.

[0015] The Chinese name of EDC / NHS solution is "1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride / N-hydroxysuccinimide solution". In some embodiments of the present invention, the electrospinning conditions in step S2 are as follows: the propulsion rate of the syringe is 0.5-0.7 mL / h, the receiving distance between the spinning receiving end and the needle of the syringe is 15-17 cm, and the voltage is 19-21 kV for electrospinning.

[0016] In some embodiments of the present invention, in step S3, chitosan and an acetic acid solution with a concentration of 0.9 to 1.1 M are used to prepare a chitosan-acetic acid solution with a concentration of 3.5 to 4.5 mg / mL; In the suspension, the concentration of the complex MQA is 18-22 mg / mL.

[0017] In some embodiments of the present invention, in step S3, after ultrasonic treatment, the pH value of the system is adjusted to 6.5-7.5, and then the electrospun type I collagen matrix Col is taken out.

[0018] Chitosan exhibits different properties under different pH conditions. When the pH value changes from acidic to neutral, chitosan forms a cross-linked network. The present invention adjusts the pH value of the system to 6.5-7.5 after ultrasound, adjusts the originally acidic conditions to neutral, and thus cross-links MQA nanoparticles to the Col surface.

[0019] In a second aspect, the present invention discloses an electrospun collagen complex, which is prepared by the above-mentioned preparation method.

[0020] In a third aspect, the present invention discloses an application of the electrospun collagen complex, wherein the application is an application in preparing a drug for preventing and / or treating dental caries.

[0021] In some embodiments of the present invention, the application is application in the preparation of a drug for promoting the biomimetic mineralization of carious tooth enamel and / or dentin and / or promoting the odontoblast differentiation of dental pulp cells.

[0022] In the present invention, the complex MQA is named according to the combination of the English initials of three raw materials: mesoporous silica MSN, polypeptide QP5, and amorphous calcium phosphate ACP; in the present invention, mesoporous silica is used to provide an integrated carrier for polypeptide QP5 and ACP, solving the problem of integrated loading and synchronous delivery of two effector substances, and utilizing the sustained-release characteristics of MSN for loaded drugs to provide the possibility for the long-term effect of QP5 and ACP on the caries lesion.

[0023] The present invention uses MSN to carry the remineralization functional polypeptide QP5 and the mineralization precursor ACP, and utilizes the electrospun type I collagen matrix as an enrichment scaffold to form an MQA-Col electrospun collagen complex, which exerts bionic repair functions such as inducing mineralization, supplying calcium and phosphorus, and regulating the behavior of dental pulp cells, thereby achieving the three-aspect repair effects of enamel and dentin bionic mineralization and dental pulp cell differentiation into odontoblasts in caries.

[0024] Compared with the prior art, the present invention has the following beneficial effects: The present invention is based on the bionic functional polypeptide QP5 with multi-directional mineralization potential, matched with the mineral precursor ACP that provides continuous controlled mineralization raw materials, enriched by porous carrier materials, and integratedly carried by the electrospun collagen matrix Col with a bionic dentin matrix structure to form an electrospun collagen complex MQA-Col, thereby achieving a bionic repair effect of caries lesions that integrates enamel bionic mineralization, dentin bionic mineralization and promotion of dental pulp cell odontoblast differentiation. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Attached Figure 1 is a process flow chart of the present invention; Attached Figure 2The transmission electron microscope and element scanning images of the composite MQA of the present invention; Figure 2 The first row from left to right includes the transmission electron microscope image, Si element distribution map, and N element distribution map. The second row from left to right includes the Ca element distribution map, P element distribution map, and S element distribution map.

[0026] Attached Figure 3 is a scanning electron microscope image of the electrospun collagen matrix Col of the present invention; Attached Figure 4 This is a scanning electron microscope image of the electrospun collagen complex MQA-Col of the present invention; Attached Figure 5 This is a graph showing the experimental results of promoting the remineralization of demineralized enamel in Experimental Example 2 of the present invention; wherein De represents the acid-etched demineralization group as a negative control, MSN represents the mesoporous silica carrier group without loading active ingredients, MQA-Col represents the electrospun collagen complex group, and NaF represents the sodium fluoride group as a positive control; Attached Figure 6 The graph is a result of the investigation test of promoting the mineralization in type I collagen fibers in Test Example 3 of the present invention; wherein each group is, from left to right, a transmission electron microscope image, a partial enlarged image of the transmission electron microscope image, and a diffraction image; Attached Figure 7 This is a graph showing the results of an investigation of the effect of promoting the remineralization of demineralized dentin in Test Example 4 of the present invention; wherein MSN represents the MSN group using mesoporous silica, MA represents the MA group using amorphous calcium phosphate-mesoporous silica, and MQA-Col represents the MQA-Col group using an electrospun collagen complex; Attached Figure 8 This is a graph showing the experimental results of investigating the effect of different concentrations of the complex on promoting the migration of human dental pulp cells in Experimental Example 5 of the present invention; Attached Fig. 9 This is a graph showing the experimental results of investigating the effects of different concentrations of the complexes in Experimental Example 6 of the present invention on promoting the differentiation of human dental pulp cells into mineralized nodules; wherein ALP represents alkaline phosphatase staining, and ARS represents Alizarin Red. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0029] The polypeptide QP5 is a prior art, and its amino acid sequence is shown in SEQ ID NO. 1 of patent publication number CN112957451A. The polypeptide QP5 used in the embodiment of the present invention is provided by Zhejiang Antolais Biotechnology Co., Ltd.

[0030] The mesoporous silica (MSN) described in the embodiments of the present invention is provided by Beijing Biotech Biotechnology Co., Ltd.

[0031] Example 1 This embodiment discloses a method for preparing the electrospun collagen complex of the present invention, and the process flow is shown in the attached Figure 1 As shown, the specific steps are as follows: S1. Preparation of complex MQA: S1.1. Add polyacrylamide hydrochloride to 500 mL of Hepes buffer (pH 7.0) containing CaCl2 at a concentration of 16 mM to obtain a PAH-CaCl2 solution, wherein the concentration of polyacrylamide hydrochloride is 580 μg / mL; S1.2, add 500 mL of 8 mM Hepes buffer (pH 5.5) containing K2HPO4 to the PAH-CaCl2 solution while stirring to obtain a PAH-ACP solution; S1.3. Mix 50 mg of peptide QP5 and 100 mg of MSN powder and add them to 25 mL of PAH-ACP solution. Stir magnetically for 23 h and then centrifuge to obtain a precipitate. Wash the precipitate with deionized water and freeze-dry it to obtain the complex MQA.

[0032] S2. Preparation of electrospinning type I collagen matrix Col: S2.1. Place the freeze-dried type I collagen sponge into a mixed solvent of hexafluoroisopropanol and acetic acid (volume ratio 0.5:1), stir until the freeze-dried type I collagen sponge is completely dissolved, and then ultrasonically vibrate for 8 min to obtain a freeze-dried type I collagen sponge solution with a concentration of 80 mg / mL; S2.2, transfer the freeze-dried type I collagen sponge solution into a 5 mL syringe, fix the syringe on a micro-pump, connect the syringe needle to the positive electrode of a high-voltage DC power supply, use a conductive metal plate at the spinning receiving end, fix tin foil on the surface and connect it to the negative electrode of a high-voltage DC power supply. Set the syringe propulsion rate to 0.5 mL / h, the receiving distance between the spinning receiving end and the syringe needle to 15 cm, perform electrospinning at 19 kV to obtain electrospun collagen; S2.3. The electrospun collagen was allowed to stand for 23 h to evaporate the solvent, and then cross-linked with glutaraldehyde vapor for 16 h. It was then soaked in a 0.1 M glycine solution for 11 h, washed with PBS buffer, and freeze-dried to obtain the electrospun type I collagen matrix Col.

[0033] S3. Preparation of the complex MQA-Col: S3.1, using chitosan and 0.9 M acetic acid solution to prepare a 3.5 mg / mL chitosan-acetic acid solution; S3.2, adding the MQA complex prepared in S1 to the chitosan-acetic acid solution to prepare an MQA-chit suspension of 18 mg / mL; S3.3. Place the electrospun type I collagen matrix Col prepared in S2 at the bottom of the porous plate, add 0.9 mL of MQA-chit suspension to each well, and then use an ultrasonic cell disruptor to sonicate for 0.9 min. Add sodium hydroxide solution to adjust the pH value of the system to 6.5, then take out the electrospun type I collagen matrix Col, wash it with deionized water and freeze-dry it to obtain the electrospun collagen complex MQA-Col.

[0034] Example 2 This embodiment discloses a method for preparing the electrospun collagen complex of the present invention, and the process flow is shown in the attached Figure 1 As shown, the specific steps are as follows: S1. Preparation of complex MQA: S1.1. Add polyacrylamide hydrochloride to 500 mL of 20 mM Hepes buffer (pH 7.0) containing CaCl2 to obtain a PAH-CaCl2 solution, wherein the concentration of polyacrylamide hydrochloride is 620 μg / mL; S1.2, add 500 mL of 9 mM Hepes buffer (pH 5.5) containing K2HPO4 to the PAH-CaCl2 solution while stirring to obtain a PAH-ACP solution; S1.3. Mix 40 mg of peptide QP5 and 120 mg of MSN powder and add them to 40 mL of PAH-ACP solution. Stir magnetically for 25 h and then centrifuge to obtain a precipitate. Wash the precipitate with deionized water and freeze-dry it for 25 h to obtain the complex MQA.

[0035] S2. Preparation of electrospinning type I collagen matrix Col: S2.1. Place the freeze-dried type I collagen sponge into a mixed solvent of hexafluoroisopropanol and acetic acid (volume ratio 2:1), stir until the freeze-dried type I collagen sponge is completely dissolved, and then ultrasonically vibrate for 12 min to obtain a freeze-dried type I collagen sponge solution with a concentration of 100 mg / mL; S2.2, transfer the freeze-dried type I collagen sponge solution into a 5 mL syringe, fix the syringe on a micro-pump, connect the syringe needle to the positive electrode of a high-voltage DC power supply, use a conductive metal plate at the spinning receiving end, fix tin foil on the surface and connect it to the negative electrode of a high-voltage DC power supply. Set the syringe propulsion rate to 0.7 mL / h, the receiving distance between the spinning receiving end and the syringe needle to 17 cm, perform electrospinning at 21 kV, and obtain electrospun collagen; S2.3. The electrospun collagen was allowed to stand for 23 h to evaporate the solvent, and then cross-linked with glutaraldehyde vapor for 20 h. It was then soaked in a 0.3 M glycine solution for 13 h, washed with PBS buffer, and freeze-dried to obtain the electrospun type I collagen matrix Col.

[0036] S3. Preparation of the complex MQA-Col: S3.1, using chitosan and 1.1 M acetic acid solution to prepare a 4.5 mg / mL chitosan-acetic acid solution; S3.2, adding the MQA complex prepared in S1 to the chitosan-acetic acid solution to prepare a 22 mg / mL MQA-chit suspension; S3.3. Place the electrospun type I collagen matrix Col prepared in S2 at the bottom of the porous plate, add 1.1 mL of MQA-chit suspension to each well, and then use an ultrasonic cell disruptor to sonicate for 1.1 min. Use sodium hydroxide solution to adjust the pH value of the system to 7.5, then take out the electrospun type I collagen matrix Col, wash it with deionized water and freeze-dry it to obtain the electrospun collagen complex MQA-Col.

[0037] Example 3 This embodiment discloses a method for preparing the electrospun collagen complex of the present invention, and the process flow is shown in the attached Figure 1 As shown, the specific steps are as follows: S1. Preparation of complex MQA: S1.1. Add polyacrylamide hydrochloride to 500 mL of 18 mM Hepes buffer (pH 7.0) containing CaCl2 to obtain a PAH-CaCl2 solution, wherein the concentration of polyacrylamide hydrochloride is 600 μg / mL; S1.2, add 500 mL of 8.4 mM Hepes buffer (pH 5.5) containing K2HPO4 to the PAH-CaCl2 solution while stirring to obtain a PAH-ACP solution; S1.3. Mix 45 mg of peptide QP5 and 100 mg of MSN powder and add them to 30 mL of PAH-ACP solution. Stir magnetically for 24 h and then centrifuge to obtain a precipitate. Wash the precipitate with deionized water and freeze-dry it to obtain the complex MQA.

[0038] S2. Preparation of electrospinning type I collagen matrix Col: S2.1. Place the freeze-dried type I collagen sponge into a mixed solvent of hexafluoroisopropanol and acetic acid (volume ratio 1:1), stir until the freeze-dried type I collagen sponge is completely dissolved, and then ultrasonically vibrate for 10 min to obtain a freeze-dried type I collagen sponge solution with a concentration of 90 mg / mL; S2.2, transfer the freeze-dried type I collagen sponge solution into a 5 mL syringe, fix the syringe on a micro-pump, connect the syringe needle to the positive electrode of a high-voltage DC power supply, use a conductive metal plate at the spinning receiving end, fix tin foil on the surface and connect it to the negative electrode of a high-voltage DC power supply. Set the syringe propulsion rate to 0.6 mL / h, the receiving distance between the spinning receiving end and the syringe needle to 16 cm, perform electrospinning at 20 kV to obtain electrospun collagen; S2.3. The electrospun collagen was allowed to stand for 24 hours to evaporate the solvent, and then cross-linked with glutaraldehyde vapor for 18 hours, then soaked in a 0.2 M glycine solution for 12 hours, washed with PBS buffer, and freeze-dried to obtain the electrospun type I collagen matrix Col.

[0039] S3. Preparation of complex MQA-Col: S3.1, using chitosan and 1 M acetic acid solution to prepare a 4 mg / mL chitosan-acetic acid solution; S3.2, adding the MQA complex prepared in S1 to the chitosan-acetic acid solution to prepare a 20 mg / mL MQA-chit suspension; S3.3. Place the electrospun type I collagen matrix Col prepared in S2 at the bottom of the porous plate, add 1 mL of MQA-chit suspension to each well, and then use an ultrasonic cell disruptor to sonicate for 1 min. Use sodium hydroxide solution to adjust the pH value of the system to 7.0, then take out the electrospun type I collagen matrix Col, wash it with deionized water and freeze-dry it to obtain the electrospun collagen complex MQA-Col.

[0040] Test Example 1 In this test example, electron microscopy was performed on the products obtained in each step of Example 3.

[0041] 1. The composite MQA prepared in step S1 of Example 3 was observed under a transmission electron microscope.

[0042] The transmission electron microscopy image of the complex MQA is shown in the attached figure. Figure 2 As shown: the MQA complex is in the form of nano-microspheres with a diameter of about 150 nm; elemental analysis shows that the MQA complex contains calcium and phosphorus from ACP and S from QP5. The results show that ACP and QP5 were successfully loaded.

[0043] 2. The electrospun collagen matrix Col prepared in step S2 of Example 3 was observed under a scanning electron microscope.

[0044] The scanning electron micrograph of the electrospun collagen matrix Col is shown in the attached figure. Figure 3 As shown: The electrospun collagen matrix Col presents a typical electrospun fiber structure, with relatively uniform fiber diameter and a small number of impurities. The results show that the Col matrix was successfully synthesized.

[0045] 3. The electrospun collagen complex MQA-Col obtained in step S3 of Example 3 was observed under a scanning electron microscope.

[0046] The scanning electron microscopy image of the electrospun collagen complex MQA-Col is shown in the attached figure. Figure 4 As shown: A large number of dense MQA nanoparticles are deposited and coated on the collagen fibers of the electrospun collagen complex MQA-Col, and MQA penetrates deep into the pores between the fibers. The results show that the MQA-Col electrospun collagen complex was successfully prepared.

[0047] The effects of the electrospun collagen complex MQA-Col of the present invention were investigated in Experimental Examples 2 to 6. The electrospun collagen complex MQA-Col used in Experimental Examples 2 to 6 was prepared according to the method of Example 3.

[0048] Test Example 2 This test example discloses an investigation test on the effect of the electrospun collagen complex MQA-Col of the present invention on promoting the remineralization of demineralized enamel. The details are as follows: Experimental groups: MSN group, MQA-Col complex group, NaF group.

[0049] The enamel samples were embedded into regular rectangular sample blocks, and the surface was polished with sandpaper and windows were opened to obtain samples with exposed enamel. Then the three groups of samples were immersed in demineralization solution for demineralization. The demineralization solution composition was as follows: 50 mM glacial acetic acid, 2.2 mM Ca(NO3)2, 2.2 mM KH2PO4, 0.5 ppm NaF, 0.1 wt% Proclin 300, and the pH was adjusted to 4.5.

[0050] After 3 days of demineralization, the samples were taken out and randomly divided into three groups, which were treated with mesoporous silica (MSN), electrospun collagen complex MQA-Col and sodium fluoride (NaF) for remineralization. Artificial saliva was used as the remineralization solution for remineralization. The enamel samples were immersed in the remineralization solution and placed on a shaker for continuous shaking. The samples were taken out at 8:00, 9:00, 14:00 and 15:00 every day and immersed in the solution of each group of materials for remineralization treatment. Each treatment lasted 5 minutes. After the treatment, they were immediately transferred to the remineralization solution. The experiment was treated for a total of 14 days.

[0051] The preparation method of each group of material solutions is as follows: a certain mass of mesoporous silica (MSN) and electrospun collagen complex MQA-Col were respectively put into Hepes buffer at pH 7.4 to prepare 5 mg / mL suspension of each group of materials, and the suspension was continuously leached at 37°C for 24 h. The supernatant was collected by centrifugation to obtain MSN group material solution and MQA-Col complex group material solution, respectively.

[0052] Sodium fluoride was separately taken and added with Hepes buffer of pH 7.4 to prepare a 5 mg / mL solution to obtain a NaF group material solution.

[0053] This treatment process simulates whether the active substances released by the complex when applied to the early enamel caries site have a remineralization and repair effect on the demineralized enamel.

[0054] After the remineralization treatment, the surface of each group of enamel samples was observed by scanning electron microscope. Figure 5 As shown: (1) After demineralization, the enamel minerals were obviously lost, the apatite inside and between the enamel columns decreased, the enamel columns had obvious outlines, the rod-shaped HAP was clearly exposed, the enamel surface showed a fish scale structure, and the cross section showed a columnar structure with distinct grooves.

[0055] (2) After remineralization, a large number of deposited mesoporous silica microspheres can be seen on the surface of the MSN group, with fewer newly formed minerals on the cross section and obvious gaps between enamel columns. A large number of newly formed minerals were observed on the surface and cross section of the MQA-Col composite group and the NaF group. The newly formed minerals in the composite group mainly grew in clusters perpendicular to the enamel columns, filling and sealing the gaps between enamel columns (indicated by the solid arrows), while the newly formed minerals in the NaF group were mainly deposited parallel to the enamel columns, with thickening of the enamel columns, but gaps still existed between the enamel columns (indicated by the dotted arrows).

[0056] The results showed that the electrospun collagen complex MQA-Col of the present invention successfully promoted the remineralization of demineralized enamel.

[0057] Test Example 3 This test example discloses an experiment to investigate the effect of the electrospun collagen complex MQA-Col of the present invention on promoting mineralization in type I collagen fibers.

[0058] Experimental groups: MSN group, MQA-Col complex group, MA group.

[0059] First, reconstitute type I collagen onto the surface of the nickel mesh: prepare a collagen assembly solution containing 50 mM glycine, 200 mM potassium chloride, pH 9.2, and a 3 mg / mL type I rat tail collagen solution, add 16.7 μL of type I rat tail collagen solution to 983.3 μL of collagen assembly solution, mix gently, and incubate at room temperature for 20 min to obtain a reconstituted collagen solution with a final concentration of 50 μg / mL. Place the nickel mesh face up in a culture dish with a wax sheet on the bottom, drop 14 μL of reconstituted collagen solution onto the surface of the nickel mesh, transfer the culture dish to a drying jar with water at the bottom, strictly seal the drying jar, and incubate in a 37°C incubator for 24 h. After incubation, remove the nickel mesh, rinse it repeatedly and gently with deionized water, air dry it naturally, and then crosslink it with 0.05 wt% glutaraldehyde at room temperature for 2 h. After crosslinking, rinse it repeatedly and gently with deionized water and air dry it again.

[0060] A certain amount of mesoporous silica (MSN), amorphous calcium phosphate-mesoporous silica (MA) and electrospun collagen complex MQA-Col were respectively put into Hepes buffer at pH 7.4 to prepare 5 mg / mL suspension of each material group. The suspension was continuously leached at 37°C for 24 h, and the supernatant was collected by centrifugation to obtain the leaching solution of each material group. The nickel mesh loaded with recombinant two-dimensional collagen was inverted on the surface of the leaching solution of each material for mineralization treatment, and the solution was changed every day. After 3 days of mineralization treatment, the nickel mesh was removed, gently rinsed with pure water and dried, and transmission electron microscopy observation and selected area electron diffraction analysis were performed.

[0061] When the mineralization process simulation complex of this test example is applied to carious dentin, whether the active substances released by it have the effect of promoting the mineral backfilling in the fibers and guiding the mineral to be arranged along the collagen fibers on the dentin collagen structure at the demineralized area.

[0062] The results are as follows Figure 6 As shown: (1) In the mineralized MSN group, only the recombinant collagen image with low density was observed, and no diffraction ring was found in the diffraction results of the collagen site, indicating that the collagen was not significantly mineralized; (2) The collagen density in the MA group was higher than that in the MSN group, but there was no diffraction ring in the SAED image, suggesting that amorphous ACP infiltration may exist at this time, but no intrafiber mineralization crystallization has yet appeared; (3) High-density collagen fibers can be observed in the MQA-Col complex group image. Diffraction at the high-density position showed (004), (002), and (211) diffraction rings, which are consistent with the characteristic diffraction rings of HAP crystals. The crystal arrangement is consistent with the fiber direction, indicating that intrafiber mineralization has occurred in the collagen fibers of the complex group.

[0063] The results show that the electrospun collagen complex MQA-Col of the present invention successfully promotes the mineralization within the fibers of two-dimensional collagen and generates new minerals arranged along the fibers.

[0064] Test Example 4 This test example discloses an experiment to investigate the effect of the electrospun collagen composite MQA-Col of the present invention on promoting the remineralization of demineralized dentin.

[0065] Experimental groups: MSN group, MQA-Col complex group, MA group.

[0066] Dentin samples were cut into blocks with a thickness of about 2 mm, and the surface was polished and ground step by step with sandpaper, and then immersed in 37 wt% phosphoric acid solution for demineralization. After 24 h of demineralization, the samples were taken out and randomly divided into three groups, which were remineralized using the extracts of mesoporous silica (MSN), amorphous calcium phosphate-mesoporous silica (MA) and electrospun collagen complex MQA-Col. The extract preparation method was as follows: a certain mass of MSN, MA and MQA-Col were respectively put into Hepes buffer at pH 7.4 to prepare a 5 mg / mL suspension of each material group, and the leaching was continued at 37°C for 24 h, and the supernatant was collected by centrifugation, which was the extract of each material group. The remineralization treatment was carried out once a day for a total of 21 days. After the remineralization treatment, the surface of the dentin sample was observed by scanning electron microscopy.

[0067] In this test example, when the mineralization process simulation complex is applied to carious dentin, whether the active substances released by it have the effect of promoting mineral deposition and sealing dentinal tubules in carious and demineralized dentin.

[0068] The results are as follows Figure 7 As shown: New minerals can be seen in all groups. A large amount of new HAP deposition can be seen in the MA group and the MQA-Col complex group, covering and sealing the exposed collagen fibers after demineralization. The surface mineral content of the MQA-Col group>MA group>MSN group. Large blocks of flat mineral deposition can be seen in the complex group (indicated by the solid arrow), accompanied by MQA nano-microspheres with mixed agglomeration of mineral crystals entering the dentinal tubules and participating in the sealing of the tubules. The cross-section shows that the MSN group still has exposed fibers in the tubules (indicated by the white arrows), the MA group has both exposed dentinal tubules (indicated by the dotted arrows) and dentinal tubules filled with new minerals (indicated by the solid arrows), and the tubules in the complex group are densely filled with minerals (indicated by the dotted arrows).

[0069] The results showed that the electrospun collagen composite MQA-Col of the present invention successfully promoted the remineralization of demineralized dentin.

[0070] Test Example 5 This test example discloses an experiment to investigate the effect of the electrospun collagen complex MQA-Col complex of the present invention on promoting the migration of human dental pulp cells.

[0071] The scratch test was used to verify the effect of the complex on promoting the migration of human dental pulp cells. 10 mg of electrospun collagen complex MQA-Col was soaked in 10 mL DMEM cell culture medium for 24 h, and the supernatant of the complex was extracted and recorded as 1 mg / mL MQA-Col extract. The extract was used as the mother liquid, and the same DMEM culture medium was used to dilute the MQA-Col extract with concentrations of 10, 50 and 100 μg / mL. Human dental pulp cells were seeded in a 6-well plate at a density of 50%. After the cell confluence reached 80%-90%, the adherent cells were streaked with a 200 μL gun tip, and 2.5 mL of different concentrations of complex culture medium were added for overnight culture. The cells were photographed under an inverted microscope after streaking and at 12 and 24 h of culture. A blank control group without the addition of complex culture medium was also set up. This experiment measured the cell migration movement and repair ability, and simulated whether the active substances released by the complex when applied deep into the caries lesion had a recruitment effect on pulp cells to promote growth and migration.

[0072] The results are as follows Figure 8 As shown: After 12 hours of culture, human dental pulp cells in each group could be observed to proliferate and migrate to the scratch site under the microscope, and the scratches were partially healed and the area was reduced, which was most obvious in the 50 μg / mL treatment group. After 24 hours of culture, the scratches in the 10μg / mL, 50μg / mL, and 100μg / mL complex treatment groups were basically closed, and the scratches in the blank control group were significantly wider than those in the complex treatment group.

[0073] The results showed that compared with the blank control group with 0 concentration, the electrospun collagen complex MQA-Col of the present invention successfully promoted the migration of human dental pulp cells.

[0074] Test Example 6 This test example discloses an experiment to investigate the effect of the electrospun collagen complex MQA-Col complex of the present invention on promoting the differentiation of human dental pulp cells into mineralized nodules.

[0075] First, prepare dental pulp cell differentiation induction medium: use α-MEM medium, add 10% fetal bovine serum, 1% double antibody, 5 nM dexamethasone, 50 μM vitamin C and 10 mM sodium β-glycerophosphate. Among them, dexamethasone, vitamin C and sodium β-glycerophosphate solutions are all filtered and sterilized with a 0.22 mm filter before preparation.

[0076] Further prepare different concentrations of MQA-Col extracts: 10 mg of electrospun collagen complex MQA-Col was soaked in 10 mL of the above differentiation induction medium for 24 h, and the supernatant of the complex was extracted and recorded as 1 mg / mL MQA-Col extract. This extract was used as the mother liquid, and the same differentiation induction medium was used to dilute and prepare MQA-Col extracts with concentrations of 10, 50, and 100 μg / mL.

[0077] Differentiation induction culture was performed on human dental pulp cells using the above-mentioned MQA-Col differentiation induction medium extract at different concentrations. Staining observation was performed after 3 days and 14 days of culture: (1) After 3 days of culture, the cells were stained with alkaline phosphatase colorimetric working solution. The reaction was terminated after obvious coloration and observation was performed under a stereomicroscope. (2) After 14 days of culture, the cells were stained with alizarin red stain. The reaction was terminated after obvious coloration and observation was performed under a stereomicroscope.

[0078] Alkaline phosphatase (ALP) staining shows the activity of alkaline phosphatase, a key enzyme in the cell biomineralization process; Alizarin red staining shows the mineral nodules produced by the cells. When the simulated complex is applied to the deep part of the caries lesion, it is determined whether the active substances released by it can promote the differentiation of dental pulp cells into odontoblasts and form mineral deposition.

[0079] The results are as follows Fig. 9 As shown: (1) Alkaline phosphatase is a key enzyme in biomineralization activities. The ALP staining results showed that the cells treated with the complex were stained darker than the control group, indicating that their ALP activity was significantly increased and the biomineralization behavior was active.

[0080] (2) Alizarin red dye can form a complex with calcium salts in a chelating manner to produce orange-red deposits. The results of Alizarin red staining showed that more calcium nodules were deposited on the cell surface after treatment with the complex, indicating that the complex induced odontogenic differentiation of human dental pulp cells and the formation of mineral nodules.

[0081] The staining results of this test example showed that compared with the blank control group with 0 concentration, the electrospun collagen complex MQA-Col of the present invention successfully promoted the differentiation of human dental pulp cells to produce biominerals.

[0082] According to the above results, it can be known that the present invention is based on the bionic functional polypeptide QP5 with multi-directional mineralization potential, matched with the mineral precursor ACP that provides continuous controlled mineralization raw materials, through MSN enrichment, and integrated support of the electrospun collagen matrix Col with a bionic dentin matrix structure to form a MQA-Col electrospun collagen complex, thereby achieving a bionic repair effect of caries lesions that integrates enamel bionic mineralization, dentin bionic mineralization and promotion of dental pulp cell odontoblast differentiation.

[0083] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solution of the present invention, but not to limit it, and certainly not to limit the patent scope of the present invention. Any changes or modifications that are made to the main design concept and spirit of the present invention without any substantial meaning, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention; in addition, the direct or indirect application of the technical solution of the present invention in other related technical fields is also included in the patent protection scope of the present invention.

Claims

1. A method for preparing an electrospun collagen complex, characterized in that: The steps include: S1. Preparation of complex MQA: S11. Preparation of PAH-Ca solution: 2+ The buffer solution is mixed with polyacrylamide hydrochloride to obtain a PAH-Ca solution; S12. Preparing a PAH-ACP solution: adding an aqueous phosphate solution to the PAH-Ca solution and mixing well to obtain a PAH-ACP solution; S13. The polypeptide QP5 and the porous carrier are added to the PAH-ACP solution, stirred, centrifuged, and the precipitate is washed and dried to obtain the complex MQA; S2. Preparation of electrospun type I collagen matrix Col: The freeze-dried type I collagen sponge was dissolved in an organic solvent to prepare a freeze-dried type I collagen sponge solution; The solution is transferred to an electrospinning method to prepare electrospun collagen; the electrospun collagen is then cross-linked, washed, and dried to obtain an electrospun type I collagen matrix Col; S3. The complex MQA is prepared into a suspension with chitosan-acetic acid solution, and the electrospun type I collagen matrix Col is immersed in the suspension, and after ultrasonic treatment, it is taken out, washed, and dried to obtain the electrospun collagen complex.

2. The method for preparing an electrospun collagen complex according to claim 1, characterized in that: The Ca-containing 2+ The buffer is a buffer containing CaCl2, and its pH value is 6.8~7.2; The phosphate aqueous solution includes a K2HPO4 buffer or a Na2HPO4 buffer, and its pH value is 5.0-6.0; The porous support includes mesoporous silica.

3. The method for preparing an electrospun collagen complex according to claim 1 or 2, characterized in that: Ca in PAH-Ca solution 2+ The concentration was 16-20 mM, and the concentration of polyacrylamide hydrochloride was 580-620 μg / mL; The concentration of phosphate in phosphate aqueous solution is 8~9 mM. The volume ratio of PAH-Ca solution to phosphate aqueous solution is 0.8~1.2:1; In step S13, the mass ratio of polypeptide QP5 to the porous carrier is 1:2-3; the mass volume ratio of the porous carrier to the PAH-ACP solution is 3-4:1, wherein when the mass unit of the porous carrier is mg, the volume unit of the PAH-ACP solution is ml.

4. The method for preparing an electrospun collagen complex according to claim 1, characterized in that: The organic solvent in step S2 includes a mixed solution of hexafluoroisopropanol and acetic acid, and the volume ratio of hexafluoroisopropanol to acetic acid is 0.5-2:1; The concentration of freeze-dried type I collagen in the freeze-dried type I collagen sponge solution is 80-100 mg / mL; In step S2, glutaraldehyde vapor volatilization cross-linking or EDC / NHS solution cross-linking is used.

5. The method for preparing an electrospun collagen complex according to claim 1 or 4, characterized in that: The electrospinning conditions in step S2 are as follows: the propulsion rate of the syringe is 0.5-0.7 mL / h, the receiving distance between the spinning receiving end and the needle of the syringe is 15-17 cm, and the voltage is 19-21 kV for electrospinning.

6. The method for preparing an electrospun collagen complex according to claim 1, characterized in that: In step S3, chitosan and an acetic acid solution having a concentration of 0.9 to 1.1 M are used to prepare a chitosan-acetic acid solution having a concentration of 3.5 to 4.5 mg / mL; In the suspension, the concentration of the complex MQA is 18-22 mg / mL.

7. The method for preparing an electrospun collagen complex according to claim 1, characterized in that: In step S3, after ultrasonic treatment, the pH value of the system is adjusted to 6.5-7.5, and then the electrospun type I collagen matrix Col is taken out.

8. An electrospun collagen complex, characterized in that: The method is prepared by any one of claims 1 to 7.

9. The use of an electrospun collagen complex according to claim 8, characterized in that: Application in the preparation of medicines for preventing and / or treating dental caries.

10. The use according to claim 9, characterized in that: Application in the preparation of drugs for promoting the bionic mineralization of carious tooth enamel and / or dentin and / or promoting the odontoblast differentiation of dental pulp cells.

Citation Information

Patent Citations

  • Preparation method and use of biomimetic anti-caries polypeptide

    CN103408653A

  • Bioactive glass composite film as well as preparation method and application thereof

    CN108186614A

  • Bioactive glass / bionic functional polypeptide complex as well as preparation method and application thereof

    CN112957451A

  • Dentin mineralization and desensitization material with mesoporous core-shell structure and preparation method of dentin mineralization and desensitization material

    CN115154331A

  • Polyelectrolyte uniformly modified intra-fiber mineralized scaffold material as well as preparation method and application thereof

    CN117771437A